Effect of inositol -stabilized arginine silicate on arthritis in a rat model - Şahin, Kazım; Ojalvo, Sara Perez; Akdemir, Fatih; Orhan, Cemal; Tuzcu, Mehmet; Şahin, Nurhan; Komorowski, James R. (Pergamon-Elsevier Science Ltd, 2019)
The purpose of this study was to test the effects of arginine-silicate-inositol complex (ASI), compared to a combination of the individual ingredients (A + S + I) of the AM, on inflammatory markers and joint health in a collagen-induced arthritis (CIA) rat model. A total of 28 Wistar rats were divided into four groups: (i) Control; (ii) Arthritic group, rats subjected to CIA induction by injection of bovine collagen type II (A); (iii) Arthritic group treated with equivalent doses of the separate components of the ASI complex (arginine hydrochloride, silicon, and inositol) (A + S + I); (iv) Arthritic group treated with the ASI complex. The ASI complex treatment showed improved inflammation scores and markers over the arthritic control and the A + S + I group. ASI group had also greater levels of serum and joint-tissue arginine and silicon than the A + S + I group. Joint tissue IL-6, NF-kappa B, COX-2, TNF-alpha, p38 MAPK, WISP-1, and beta-Catenin levels were lower in the ASI group compared to the other groups (P < 0.05 for all). In conclusion, these results demonstrate that the ASI complex may be effective in reducing markers of inflammation associated with joint health and that the AM complex is more effective than a combination of the individual ingredients.
Keywords: Arthritis; Arginine; Silicate; Inositol; Inflammatory cytokines